Study of the influence of some physical factors on the viability of seeds of Echinaceae pallida variety “Lebedushka” - Gavrilkova, E.A.; Tleukenova, S.U.; Ramazanov, A.K.; Zhumina А.G.; Seldugayev О.B.; Zinovjev L.А. (Fundamental and Experimental Biology, 2023)
Application of physical factors allows activating seed germination and increasing plant yield. The article presents data on testing of germination parameters of seeds of Echinaceae pallida variety “Lebedushka” under the influence of physical factors. Seeds were preliminarily immersed in liquid nitrogen for a day, and then subjected to laser irradiation, babbling and magnetic fields for a certain time. As a result of the experiments, it was determined that exposure to a constant magnetic field promoted a reliable increase in germination rates by 10.4 % compared to the control. The best germination was determined in seeds exposed to a constant magnetic field with an induction of 75 µTesla for 3 days, without prior cryopreservation (90.0 %). In the experiments with bubbling, the best germination was determined in seeds without cryopreservation ‒ 75.25 %, and in the variant of the experiment with He-Ne laser irradiation for 2 minutes without preliminary immersion in liquid nitrogen vapor ‒ 95.0 %.